2013
DOI: 10.5005/jp-journals-10008-1133
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnostics and Genetic Counseling in Primary Congenital Glaucoma

Abstract: Primary congenital glaucoma (PCG) is a childhood irreversible blinding disorder with onset at birth or in the first year of life. It is characterized by the classical traid of symptoms viz. epiphora (excessive tearing), photophobia (hypersensitivity to light) and blepharospasm (inflammation of eyelids). The only anatomical defect seen in PCG is trabecular meshwork dysgenesis. PCG shows autosomal recessive mode of inheritance with considerable number of sporadic cases. The etiology of this disease has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…An analysis of CYP1B1 in Brazilian patients with PcG showed that four of the nine mutations were present as compound heterozygotes, two in homozygotes and only one mutant allele was identified in three of the cases. in one patient, the c.8147c>T (p.P437l) and c.8182delG mutations were identified in a compound heterozygote, and clinical examination revealed a highly compromised phenotype with low visual acuity and difficultly controlling ioP (13). Screening of CYP1B1 and LTBP2 in Saudi families with PcG showed that PcG cases with CYP1B1 variants, including p.P437l, had a more severe subepithelial haze in cornea and a greater c/d ratio compared with those cases with no identified mutation (32).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…An analysis of CYP1B1 in Brazilian patients with PcG showed that four of the nine mutations were present as compound heterozygotes, two in homozygotes and only one mutant allele was identified in three of the cases. in one patient, the c.8147c>T (p.P437l) and c.8182delG mutations were identified in a compound heterozygote, and clinical examination revealed a highly compromised phenotype with low visual acuity and difficultly controlling ioP (13). Screening of CYP1B1 and LTBP2 in Saudi families with PcG showed that PcG cases with CYP1B1 variants, including p.P437l, had a more severe subepithelial haze in cornea and a greater c/d ratio compared with those cases with no identified mutation (32).…”
Section: Discussionmentioning
confidence: 96%
“…even though most cases of developmental glaucoma seem to be sporadic, up to 40% of cases are considered to be genetically inherited, demonstrating an autosomal recessive inheritance pattern with variable penetrance (11,12). Mutations in the genes, CYP1B1, LTBP2 and TEK have been reported in patients with developmental glaucoma, and among these, mutations in CYP1B1 are the most commonly reported (13)(14)(15). CYP1B1 is a drug-metabolizing enzyme of the cytochrome P450 gene family, which is expressed in a wide spectrum of tissues, including the iris, trabecular meshwork (TM), ciliary body and anterior uveal tract of the eye (16).…”
Section: Discussionmentioning
confidence: 99%
“…Familial cases of glaucoma are most often associated with mutations in the CYP1B1 gene (encoding cytochrome P450 enzyme 1B1) located in the GLC3A region [13][14][15]. Although not all cases of PCG are genetically determined, children diagnosed with it should be referred to a genetic counseling center [16].…”
Section: Etiologymentioning
confidence: 99%
“…We have already reviewed the molecular biology, diagnostic aspects, and genetic counseling protocols in primary congenital glaucoma. [5] The second part of the issue emphasizes that very little can be done to rescue or restore vision. Therefore, novel therapies that address glaucoma beyond IOP need to be identified to develop effective strategies.…”
mentioning
confidence: 99%